Design of a Web-Based Accounting Information System to Improve Transparency and Accountability - Teguh Hidayat; Muhammad Rivandi; Muhammad Abulwafa; Wilfah Busri Wahyu (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2026)
Schools have a responsibility to manage their finances in accordance with applicable financial management principles, such as transparency, accountability, fairness, and efficiency. At Sutera State High School No. 2, financial management involves various funding sources allocated to a number of budget items, thus requiring an integrated and structured management system. To support cash flow control and the provision of accurate and timely financial information, an information system is needed that can generate financial reports in real time and be accessed by authorized decision-makers. This study aims to design a web-based accounting information system that can support the school’s budget management and implementation processes. The method used was the research and development (R&D) approach, employing the waterfall system development model. After the system design and testing phases were completed, the researchers collaborated with school officials to provide training and guidance on using the system. The research results show that the web-based financial information system developed simplifies cash flow management for financial staff and allows the principal to access financial reports directly. Thus, the designed system supports the realization of more transparent, effective, and accountable financial management at Sutera State High School No. 2. In addition to making it easier to prepare financial reports, this system also helps minimize data entry errors and speeds up the process of presenting financial information. It is hoped that this web-based accounting information system will serve as a solution to support more modern, efficient, and sustainable school financial management.